The Romance between Greece and the East - Whitmarsh, Tim; Thomson, Stuart (Cambridge Univ. Press, 2013)
Twenty essays by renowned scholars explore contact between Greece and the Ancient Near East through the medium of prose fiction
Includes bibliographical references and index
Keywords: Greece -- Civilization -- Middle Eastern influences; Aufsatzsammlung; Einfluss; Naher Osten; Roman; Novelle; Griechisch